Kunst in opdracht, 1999-2005 : kunstopdrachten door de kunstcel van de Vlaamse Bouwmeester - Laenen, Katrien; Bijl, Guillaume; Devos, Danny; Hoste, Pol; Lambrecht, Luk; Luyckx, Filip; Neville, Mark; Van Rossem, Patrick (Brussel : Vlaams Bouwmeester, 2006)
Bijl, Guillaume ; Maes, Annemie ; Nölle, Annick ; Neville, Mark ; De Leener, Hugo ; De Cupere, Peter ; Devos, Danny ; Vangrunderbeek, Dimitri ; Grigely, Joseph ; Rogiers, Peter ; Körmeling, John ; Van Kerckhoven, Anne-Mie ; Voordeckers, Jürgen ; Meuris, Wesley ; Pereira Eires, Joaquim ; Speakman, William ; Calogero, Burgio ; Vermeir, Katleen ; Terlinden, Christophe ; Mertens, Natalie ; Vansant, Tom ; Rothuizen, Jan ; Jacobs, Laure-Anne ; Verwimp, Joël ; Vandermeulen, Bruno ; Claeyé, Catherine
boek